The Moderating Effect of Social Capital on Fiscal Policy Responses to COVID- 19: Cross-Country Evidence - Gömleksiz, Mustafa; Altıntaş, Kıvanç (Panoeconomicus, 2023)
This study suggests that an adequate level of social capital with a robust health profile might be associated with positive policy outcomes in combating COVID-19. We investigate the effect of interaction between fiscal policy responses and social capital on the spreading of the pandemic, by considering the country health profile, demographic and economic factors, in a cross-section of 94 countries. Firstly, the results of the analysis indicate the moderating effect of social capital on keeping the pandemic under control through fiscal policy measures. In particular, strong bilateral and family ties as well as better coordination and cooperation at the community level can facilitate the goal of fiscal policy measures. The results also reveal that the declining effect of fiscal policy on the pandemic mostly arises from the relatively high social capital levels, while it loses its effectiveness at low levels. Secondly, the findings emphasize the role of behavioural risk factors, care systems and preventative interventions as prominent determinants of surviving in pandemic. Thirdly, we conclude that taking specific measures for identified vulnerable and high-risk groups is quite important in overcoming the disease.Key words: COVID-19, Pandemic, Social capital, Fiscal policy.JEL: C1, H3, H8.